Academic Senate Minutes 2004-09-30 - Academic Senate:::::::::
Chair Report and Correspondence. Agenda approved. Minutes of 9/16/04 approved. Changes to Nursing MS approved. Revision of Single Subject Waiver Program in English approved. Misconduct in Research Policy approved. Faculty Emeritus Policy approved. Course Outline Policy first reading. Procedures for Faculty Trustees Nomination referred to Structure & Functions. Questions for President. Reports from Associated Students, Statewide Senator, APC, EPC, FSAC, SAC, Senate Budget committee.